Ghalib: A Representative of His Era - Sajid, Shazia; Butt, Faiza (sourcecoder, 2023)
Mirza Ghalib is a renowed poet in Urdu Lierature, celeberated for his distinctive ideology of life. He transcends temporal boundaries by considering the past, present, and future as an interconnected continuum. His poetry beautifully interwines the richness of tradition with the evolving essence of the present. This article delves into how Ghalib’s poetic oeuvre encapsulates the prevailing life ideology of his era, offering a profound representation of the cultural tapestry, political tension, religious convictions, and economic nuances. By shedding light on the multifaceted dimensions of his work, this article provides a deeper understanding of its significance in portraying the conditions and ethos of his time.